PENGARUH PENGUNGKAPAN MODAL INTELEKTUAL TERHADAP BIAYA MODAL EKUITAS - Vista Anggraeni, Anindita; Indarti, Maria Goreti Kentris (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2021)
The cost of equity capital is the rate of return expected by investors, which must bepaid by the company as a form of return on the capital provided by investors to thecompany. This study examines the effect of intellectual capital disclosure and its threecomponents, namely human capital disclosure, structural capital disclosure, andrelational capital disclosure on the cost of equity capital. The population in this studyare banking sector companies listed on the Indonesia Stock Exchange in 2015-2019.Based on the purposive sampling method, 165 data were obtained. The test resultsusing ordinary least square regression showed that the disclosure of intellectualcapital, disclosure of human capital, disclosure of relational capital had a significantnegative effect on the cost of equity capital. However, the disclosure of structuralcapital has no effect on the cost of equity capital